2017
DOI: 10.4081/ripppo.2017.257
|View full text |Cite
|
Sign up to set email alerts
|

From turn-by-turn to larger chunks of talk: An exploratory study in psychotherapeutic micro-processes using conversation analysis

Abstract: Independent of theoretical orientation therapies of all kind are talk-in-interaction. Influential overall conceptualizations (as e.g. intervention) belong to a certain model of medicalizing the psychotherapeutic endeavor. Talk-in-interaction is the base for applying Conversation Analysis (CA) in psychotherapeutic process research. CA is a powerful tool originating from social science taking data, hypotheses and theories from careful observing in a similar way as infant observers did. The common discovery is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Since then, the study of emotion, empathy, and affiliation have become even more central in conversation analysis of psychotherapy (see, e.g., Voutilainen et al, 2010a;Ekberg, Shaw, Kessler, Malpass, & Barnes, 2016;Muntigl & Horvath, 2014a, 2014bMuntigl, Knight, Watkins, Horvath, & Angus, 2013;Weiste & Peräkylä, 2014). Furthermore, conversation analytical research is increasingly addressing questions and concerns of clinical relevance (see, e.g., Buchholtz, Spiekermann, & Kächele, 2015;Buchholz & Kächele, 2017;Lepper, 2009;Sutherland, Peräkylä, & Elliott, 2014).…”
Section: The Double Task Of Ca In Research On Psychotherapy: Overviewmentioning
confidence: 99%
“…Since then, the study of emotion, empathy, and affiliation have become even more central in conversation analysis of psychotherapy (see, e.g., Voutilainen et al, 2010a;Ekberg, Shaw, Kessler, Malpass, & Barnes, 2016;Muntigl & Horvath, 2014a, 2014bMuntigl, Knight, Watkins, Horvath, & Angus, 2013;Weiste & Peräkylä, 2014). Furthermore, conversation analytical research is increasingly addressing questions and concerns of clinical relevance (see, e.g., Buchholtz, Spiekermann, & Kächele, 2015;Buchholz & Kächele, 2017;Lepper, 2009;Sutherland, Peräkylä, & Elliott, 2014).…”
Section: The Double Task Of Ca In Research On Psychotherapy: Overviewmentioning
confidence: 99%
“…Research has already demonstrated that, to achieve an elaborate understanding of how therapeutic projects actually unfold over time, it is important to examine longer stretches of interaction, to ascertain whether certain therapeutic interventions are functioning in a more (or less) productive way (e.g., Voutilainen et al, 2011;Muntigl, 2013;Buchholz and Kächele, 2017). This paper has shown that a client's distress may need to be managed over many sequences and that the ways in which distress is dealt with in one interactional phase may occasion different responses from the therapist.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we expanded the focus of analysis from brief interactional sequences to longer stretches of talk spanning the whole session in an attempt to track the development of meanings over time (Buchholz and Kächele, 2017). This 'zooming out' allowed us to observe what, from a psychoanalytic perspective, would be considered the process of free association.…”
Section: Discussionmentioning
confidence: 99%